Determination of Effective Thermal Properties of Open Cell Ceramic Foam - Abdulhassan A. Karamallah; Ali Mohammed Hussein (Engineering and Technology Journal, 2014)
This work presents an experimental investigation for effective thermal properties of open cell ceramic foam (80.13 Al2O3, 17.79 SiO2, 1.57 MgO, and 0.51 Na2O. % weight),which were measured using the Transient Plane Source (TPS) technique, and the parameters, which influenced them, and the influence of foam structure. Three types of pore per inch (ppi) were tested (10, 30 and 50). Three sensors were used, K5599 (of 60 mmdiameter), K4922 (of 30 mmdiameter) and K5501 (of 13 mmdiameter).The percentage difference between the highest and lowest results for each sensor and ppi are: for K5501 sensor were 34% in 10 ppi, 15% in 30 ppi and 18% in 50 ppi, for sensor K4922 were 19%, 11% and 13%, respectively, and for K5599 were 17%, 14% and 16%, respectively. The results show that the sensor K4922 is the more suitable sensor to test such material especially which has high ppi.